The Psychological Dimension of Space in the Poetry of Diwan al-Jinn al-Homsi (d. 235 AH): A Critical Study (Journal of the College of Basic Education, 2025)
Reading literary texts through the psychological approach is not isolated from critical readings through other approaches, whether textual approaches like structuralism, stylistics, reception theory, or discourse analysis, or contextual approaches such as historical and social criticism. Psychological readings also aim to establish a relationship with the reader and capture their attention by delving into the depths of the text, exploring subconscious elements and the repression of psychological instincts.This is particularly significant in the poetry of a poet oscillating between anxiety, fear, psychological deterioration, profound sadness, and mood swings. This does not suggest that his poetic language is ineffective; on the contrary, his creative work is distinguished by artistic imagery, aesthetic qualities, delicate style, and solid stylistic structures. Through these, he accurately depicted his fluctuating psychological and emotional states and unveiled his subconscious dimensions, particularly in the structure of space. This structure revealed several psychological dimensions that the poet experienced. For example, when describing the grave as a tangible physical space, his motivations and dimensions differ from those evident in his descriptions of metaphorical spaces or his outright rejection of psychological spaces.The aim of this study is to interpret and analyze the texts to reveal their references, internal struggles, and subconscious elements rooted in the poet’s psyche, all shaped by his psychological experiences and expressed through space using the psychological critical approach.Thus, the psychological dimension of space serves as an artistic tool through which the poet constructs the psychological stance he feels toward the other being described.